Human Relations in Industry - Tousignant, Fabienne (Relations industrielles / Industrial Relations, 1953)
The article reviews "Human Relations in Industry," by Ralph N. Campbell. Reprint Series Number 15, New York State School of Industrial and Labor Relations at Cornell University (5 pages).